CRYSTAL STRUCTURE OF NA4[CU4O2(SO4)4]·MECL (ME: NA, CU, []) - THE SYNTHETIC NA-ANALOGUE OF PIYPITE (CARATIITE) - Kahlenberg V.; Piotrowski A.; Giester G. (My University, 2000)
The crystal structure of Na4[Cu4O2(SO4)4] MeCl (Me: Na, Cu, Box) has been solved by direct methods and refined to R1 = 0.028 using 2466 independent reflections. The compound is tetragonal with space group P4/n, a = 18.451(1) Å, c = 4.9520(2) Å, Z = 4. The two main building units running parallel to the c-axis comprise: (1) slabs containing SO4 and OCu4 tetrahedra; and (2) chains of corner sharing Me(Cl,O)6 octahedra. The displacement ellipsoids of the atoms occupying the Me sites and of the Cl ions indicate a short-range static disorder. Copper in the slabs exhibits a (4+1) coordination. Both elements form a tunnel structure in which additional Na atoms are incorporated for charge compensation. The structure is closely related to the mineral piypite (K4Cu4O2(SO4)4 MeCl (Me: Na, Cu, Box)): a ≈ √ 2 . apiy.; c ≈ cpiy.. Furthermore, the structure has a pronounced pseudo-translational symmetry: apart from some of the oxygen sites, all of the nineteen crystallographically distinct positions are related by a pseudo F centring.